Correlation of Platelet-Lymphocyte Ratio (PLR) as 28-Days Sepsis Mortality Predictor in Intensive Care Unit of RSMH Palembang - Tiara Santi Rizal; Fredi Heru Irwanto; Rizal Zainal; Mgs Irsan Saleh (HM Publisher, 2020)
Introduction. Inflammatory and anti-inflammatory response are important in pathophysiology and mortality of sepsis. Platelet as first line inflammatory marker was found increasing during early phase of infection. Decrease in lymphocyte was caused by disrupted balance between inflammatory and anti-inflammatory response. Platelet-to- lymphocyte ratio (PLR) is a cheap and accessible biomarker of sepsis mortality. This study aims to find the sensitivity and specificity of PLR as mortality predictor of sepsis in 28 days. Methods. This observational analytic study with retrospective cohort design was conducted to 91 sepsis patients in intensive care unit of Dr. Mohammad Hoesin Palembang Central Hospital between January and December 2019. Samples were secondarily collected from medical record during June-July 2020. Data was analyzed using chi-square test, cog regression test, and ROC curve analysis. Results. The result found 50 patients (54,9%) died in 28 days. Morbidity score (Charlson) was the only statistically significant mortality parameter (p=0,009). The study reported PLR cut-off point of >272,22. The sensitivity and specificity of PLR as 28-days sepsis mortality predictor are 84% and 80,49% respectively. Conclusion. PLR is alternatively reliable mortality predictor in sepsis patient, accounted to its relatively high sensitivity and specificity.